2021
DOI: 10.1155/2021/5560915
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin Targets PI3K and mTOR and Inhibits Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM), the most common malignant primary brain tumor, has a very poor prognosis. With increasing knowledge of tumor molecular biology, targeted therapies are becoming increasingly integral to comprehensive GBM treatment strategies. mTOR is a key downstream molecule of the PI3K/Akt signaling pathway, integrating input signals from growth factors, nutrients, and energy sources to regulate cell growth and cell proliferation through multiple cellular responses. mTOR/PI3K dual-targeted thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 65 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…It has been found that taxifolin have effect of treatment on primary malignant brain tumor by inhibited mTOR/PI3K, promoted autophagy and suppressed lipid synthesis in GBM [ 35 ]. In addition, taxifolin also have a cardioprotective effect on diabetes cardiomyopathy by inhibiting oxidative stress and cardiomyocyte apoptosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that taxifolin have effect of treatment on primary malignant brain tumor by inhibited mTOR/PI3K, promoted autophagy and suppressed lipid synthesis in GBM [ 35 ]. In addition, taxifolin also have a cardioprotective effect on diabetes cardiomyopathy by inhibiting oxidative stress and cardiomyocyte apoptosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taxifolin has been shown to inhibit GBM in mice in vivo experiments. Taxifolin is considered to be a valuable drug for the treatment of GBM by W et al ( Yao et al, 2021 ).…”
Section: Therapeutic Effects Of Taxifolinmentioning
confidence: 99%
“…This results in the suppression of apoptosis. Subsequently, activated Akt by mediating protein synthesis activates mTOR (downstream target of PI3K) [ 92 ]. Hyperactivation of the PI3K/Akt pathway in GBM induces both the rapid growth of tumors and multidrug resistance.…”
Section: Main Pharmacological Options In the Treatment Of Glioblastomamentioning
confidence: 99%